Obinutuzumab treatment in the elderly patient with chronic lymphocytic leukemia - Seiter K (Dove Medical Press, 2015)
Karen Seiter, Aleksandra Mamorska-DygaDepartment of Medicine, Division of Hematology/Oncology, New York Medical College, Valhalla, NY, USA Abstract: Chronic lymphocytic leukemia (CLL) is the most common leukemia in adults in Western countries. Fludarabine-based regimens demonstrate higher response rates in younger patients but have a significant risk of infection and are thus poorly tolerated by older, frail patients. Anti-CD20 monoclonal antibodies have added to the efficacy of chemotherapy in CLL. Obinutuzumab is a potent Type II anti-CD20 monoclonal antibody with enhanced antibody-dependent cellular toxicity and direct cell death compared with rituximab. In Phase I studies, infusion reactions and neutropenia were the predominant toxicities. Phase II studies demonstrated efficacy both as a single agent and in combination with chemotherapy in patients with CLL. The CLL11 trial was a Phase III randomized trial of chlorambucil alone or with either obinutuzumab or rituximab in elderly, unfit patients. Progression-free survival (the primary end point) was 26.7 months for patients receiving obinutuzumab plus chlorambucil versus 16.3 months for those receiving rituximab plus chlorambucil and 11.1 months for those receiving chlorambucil alone (P<0.001). Overall survival was improved for patients receiving obinutuzumab plus chlorambucil versus chlorambucil alone (P=0.002). This trial led to the US Food and Drug Administration (FDA) approval of obinutuzumab in this patient population.Keywords: chronic lymphocytic leukemia, obinutuzumab, chlorambucil, elderly